The concept of time of young children in a rural community - Aguilar, Nona Cacho (2000)
This study on concept of Young Children in rural community is a qualitative study. It attempted to explain and identify the time concepts of young children, as well as looked for variations of the concept of time from the two groups involved, and investigated if cognitive ability affected the concept of time. Four attributes of time were identified: sequence, clock, calendar, and duration. This explanatory study strived to anchor on the three theories of human development, namely, the Piaget's Theory of Cognitive Development, the Vygotsky's theory of Cognitive Development. Involved in this study are 43 children, ages 6-10 years, all enrolled in public school. They belong to the two groups, the fishing group and the farming group. The farming group comes from Barangay Mabini, a farming area of the town San Jose, where the main occupation of the residents are farming or related to farming. There were 24 pupils from this group. The fishing group comes from Barangay Caminawit, the fishing area of the same town. This group has 19 children. Convenience and purposive sampling were utilized in determining the sample of this study. Four instruments were used to gather the data, namely, the Raven's Standard Progressive Matrices (SPM), The Pupil's Information Sheet (PIS), The Time Pictorial Test (TPT), and the Interview Schedule. All instruments, except the Raven's Standard Progressive Matrices were developed by the researcher. Responses gathered were analyzed quantitatively and qualitatively. The accuracy and inaccuracy of responses from the Pictorial Test were quantitatively analyzed and the use of percentage was utilized. Responses from the Interview were qualitatively analyzed according to the quality of the responses and were then categorized under answer categories. Findings also showed that personal experiences, personal-related activities, and community orientation were found to greatly affect the concept of time in all four time attributes. Lastly, it was found out that social environment appears to be a dominant factor in learning the concept of time compared to cognitive ability.